Effectiveness of Psychological Support Based on Positive Suggestion with the Ventilated Patient - Szilágyi, Adrienn K.; Diószeghy, Csaba; Benczúr, Lilla; Varga, Katalin (European Journal of Mental Health, 2007)
The purpose of intensive care is recovery from the critical state with the best possible quality of life. Lengthy therapy with its physical and psychological complications and iatrogen effect may spoil the expected outcome. The positive effect of the psychological support of the patient that can be proven empirically has been applied and examined in the present study. In the present prospective, randomised, controlled study the patients – mechanically ventilated for more than 48 hours – of two intensive care units of Budapest have been examined. In the study they were given psychological support based on positive suggestions (PSBPS) using their susceptibility induced by the situation, complementing their somatic treatment. Altogether 60 persons have been examined (27 in the control, 33 in the suggestion group). The result showed a statistically significant 2.5 day shorter ventilation period (p < 0.04). The length of stay (LOS) in the intensive care unit (ICU) was also reduced by 4 days in the group who received suggestions. If the patient was treated by the same psychologist during at least 50% of the ICU stay, both parameters were reduced by 3.5 days at a significance level of p < 0.01. In the case of those patients with the same psychologist who died during the study, it was mainly their age and state that contributed to their death. Their dying was 4.5 days shorter or they left the ICU sooner than the control group members, in whose case lengthy ventilation was typical.